Ischemic preconditioning - Ristić-Anđelkov Anđelka; Baškot Branislav; Damjanović Milorad; Rafajlovski Saša I. (Vojnosanitetski Pregled)
Background. Ischemic preconditioning is a phenomenon during which myocardium, subjected to brief episodes of ischemia followed by reperfusion, tolerates better the subsequent, more prolonged episode of this ischemia, thus reducing the infarction size substantially. Case report. Two patients with acute left anterior descendent artery occlusion received fibrinolytic therapy (alteplase) within 6 hours of the onset of chest pain, but developed myocardial infarctions of different sizes. The first patient, without the history of preinfarction angina, developed large anterior infarct, because there was no time either for ischemic preconditioning or for the coronary collateral vessels development. In the second patient, with 4-day history of preinfarction angina, the more favorable outcome was seen he developed smaller apical necrosis, with the great degree of myocardial viability in the infarct-related area. Conclusion. Ischemic preconditioning in patients with acute myocardal infarction results in the reduction of mortality, infarction size, as well as in the frequency of malignant arrhythmias.